A Qualitative Exploration of Choral Singing in Community-dwelling Older Adults. (May 2020) - Petrovsky, Darina V.; Sefcik, Justine S.; Cacchione, Pamela Z.
Recent research has recognized the value of participatory arts, including choirs, as a strategy to engage older adults in the community. Less is known about the participation of minority older adults of low socioeconomic status (SES) in choirs. The purpose of this qualitative descriptive study was to explore the perceived benefits of choral singing among older adults from Program of All-Inclusive Care for the Elderly (PACE) day centers. We elicited perceptions from 19 choir participants from three focus groups, the majority of whom were Black or African American (N =17/19), each held at a different PACE center. One main theme emerged, "Something for us to do that we love, " with two subthemes, "Joyful time together" and "Uplifting experience performing for others." These study findings have implications for promoting choir singing in older adults to serve as a place for engagement in social interactions in a lifelong activity they love.